Humanizing the Digital Panopticon: Islamic Social Capital, Algorithmic Management, and Social Sustainability in the Gig Economy - Unna Ria Safitri; Lio Bijumes; Fuad Dhiya Ul Husaen; Safia Bibi (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: This study investigates how Islamic Social Capital humanizes digitally controlled gig work systems characterized by algorithmic surveillance and performance monitoring. In many platform-based labor environments, worker sustainability is often explained through technological efficiency and performance metrics, while relational and moral dimensions remain underexplored. Drawing on the Job Demands–Resources framework and digital labor theory, this research aims to examine the direct, mediating, and moderating mechanisms linking Islamic Social Capital, Psychological Safety, Collaborative Resource Sharing, Algorithmic Management Intensity, and Social Sustainability Performance among gig workers operating under algorithmic management systems.Methods: A quantitative survey was conducted with 237 app-based gig workers. Data were analyzed using structural equation modeling to test the proposed structural relationships, including mediation and moderation effects.Results: Islamic Social Capital significantly enhances Psychological Safety, Collaborative Resource Sharing, and Social Sustainability Performance. Psychological Safety and Collaborative Resource Sharing partially mediate the relationship between Islamic Social Capital and Social Sustainability Performance, with psychological pathways showing stronger effects. Algorithmic Management Intensity strengthens the positive relationship between Islamic Social Capital and Psychological Safety but does not significantly moderate collaborative behaviors.Conclusion and suggestion: Sustainable performance in digitally governed gig ecosystems depends not only on technological systems but also on morally embedded relational capital. Platform governance strategies should integrate transparency, fairness, and community-based relational infrastructures to enhance psychological security and long-term sustainability.